Boosting sustainable water production by upstream integration of desalination with saltworks in the Mediterranean region - A. Campione; M. Salem; S. Chamam; F. Vicari; R. Cucchiara; A. Hannachi; D. Pastorelli; A. Cipollina (Desalination and Water Treatment)
SEArcularMINE is an EU project that is focused on mineral extraction from saltwork bitterns, adopting a circular approach. Within this context, this work shows the possibility of completing the circular scheme with an upwind integration of seawater desalination that can provide freshwater to the local community but also use the brine reject to feed the saltwork in order to increase its productivity. In this study, a specific case of a natural saltwork in Trapani (Italy) is presented, assuming to place a desalination plant very close to the saltworks, so that the brine can be sent there without an additional energy input. After choosing the best desalination technology, demonstrating that Reverse Osmosis (RO) is more suitable than thermal processes from both economic and environmental point of view, the details of the RO design are presented. Then, preliminary calculations using a simple model for the saltwork ponds have been performed, showing that the brine feed can either increase the salt productivity by more than 50% or that the ponds surface can be reduced by more than 40%. Finally, evaporation experiments on desalination brines have been performed to demonstrate that no changes in salt quality occur compared to the standard seawater feed.